1994
DOI: 10.1029/94jc02066
|View full text |Cite
|
Sign up to set email alerts
|

Upper layer circulation in the western tropical North Atlantic Ocean during August 1989

Abstract: Shipboard acoustic Doppler current profiler velocity measurements and profiles of temperature, salinity, and dissolved oxygen measurements are used to map the flow field above the cr 0 = 26.8 isopycnal (approximately the upper 300 m of the water column) in the North Brazil Current (NBC) retroflection region (0 ø to 14øN, 60 ø to 40øW) during August of 1989. The water column is divided into a near-surface, upper thermocline layer (above cr 0 = 24.5) and a main to subthermocline layer (or 0 = 24.5 to cr 0 = 26.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 12 publications
4
58
0
1
Order By: Relevance
“…The NECC is heavily supplied via cross-equatorial in flow during July to December or January, expressed by a strong surface current retroflection near 3°-5°N [Johns et al, 1990;Didden and Schott, 1992], while in spring to early summer the NECC is weak or even flowing westward [ Richardson and Reverdin, 1987]. The NECC can also be supplied from the north, as was determined by Wilson et al [1994] for August 1989, when significant transports out of the NEC turned south ward near the western boundary and joined the NECC. Part of this NEC recirculation even transited through the eastern Car ibbean.…”
Section: I Introductionmentioning
confidence: 92%
“…The NECC is heavily supplied via cross-equatorial in flow during July to December or January, expressed by a strong surface current retroflection near 3°-5°N [Johns et al, 1990;Didden and Schott, 1992], while in spring to early summer the NECC is weak or even flowing westward [ Richardson and Reverdin, 1987]. The NECC can also be supplied from the north, as was determined by Wilson et al [1994] for August 1989, when significant transports out of the NEC turned south ward near the western boundary and joined the NECC. Part of this NEC recirculation even transited through the eastern Car ibbean.…”
Section: I Introductionmentioning
confidence: 92%
“…However, the North Brazil Current System and lately the Caribbean passages have been studied extensively in recent years (Brown et al, 1992;da Silveira et al, 1994;Johns et al, 1990;Richardson, 1994;Richardson et al, 1994;Schott et al, 1995;SR9l;Wilson and Johns, 1996;Wilson et aL., 1994), so that a clearer picture is emerging. One schematic of the upper level currents at low latitudes in the North Atlantic is shown in Figure 1-74.…”
Section: On the Tropical Atlanticmentioning
confidence: 99%
“…Wilson et al (1994) and Bourlès et al (1999) identified three different origins for the water masses at the upper western equatorial Atlantic: North Atlantic Water (NAW), South Atlantic Water (SAW), and Eastern tropical Atlantic Water (EAW). The NAW originates in the subtropical region of the northern hemisphere and is advected towards the equator by the North Equatorial Current (NEC).…”
Section: Criteria For Determining Isothermal Mixed and Barrier Layersmentioning
confidence: 99%
“…1). The T/S references used to identify the water masses were obtained from Wilson et al (1994) and Bourlès et al (1999). Particular attention is given to those areas where SMW cores are observed between the 24.5 and 26.25 isopycnals.…”
Section: Criteria For Determining Isothermal Mixed and Barrier Layersmentioning
confidence: 99%